A New Hybrid Finite Element Method: Electromagnetic Propagation in Bent Waveguides - Joao Paulo N. Torres; V. Malo Machado; Antonio Baptista (IEEE Photonics Journal)
A new hybrid finite element method (HFEM) was developed, using basis functions of first and second order, to analyse the electromagnetic wave propagation in three types of waveguides: disk waveguides, ring waveguides and cylindrical waveguides. For validation purposes, results obtained with the HFEM method were compared with those obtained with a recursive finite element method (RFEM) and with two different analytical methods. The domain discretization effect on the results of the new HFEM method was examined using either a uniform distribution of nodes or a Delaunay distribution method. The results show that the Delaunay method, used in the mesh definition, is important, not only to assure the reliability of the method but also to significantly reduce the computation time and memory consumption. Also, the influence of the distance between the fictitious boundary and the waveguide core was analysed showing an important effect on the result numerical accuracy. In conclusion, results show that the new hybrid finite element method presented has a significant advantage on calculation time over the recursive finite element method.